Geochronological constraints on the Late Proterozoic to Cambrian crustal evolution of eastern Dronning Maud Land, East Antarctica: a synthesis of SHRIMP U–Pb age and Nd model age data - Shiraishi, K.; Dunkley, Daniel; Hokada, T.; Fanning, M.; Kagami, H.; Hamamoto, T. (Geological Society Publishing House, 2008)
In eastern Dronning Maud Land (DML), East Antarctica, there are several discrete, isolated magmatic and high-grade metamorphic regions. These are, from west (c. 20degE) to east (c. 50degE), the Sør Rondane Mountains (SRM), Yamato–Belgica Complex (YBC), Lutzow-Holm Complex (LHC), Rayner Complex (RC) and Napier Complex (NC). To understand this region in a Gondwanan context, one must distinguish between Pan-African and Grenvillian aged magmatic and metamorphic events. Sensitive high-resolution ion microprobe U–Pb zircon ages and Nd model ages for metamorphic and plutonic rocks are examined in conjunction with published geological and petrological studies of the various terranes. In particular, the evolution of the SRM is examined in detail. Compilation of Nd model ages for new and published data suggests that the main part of eastern Dronning Maud Land, including the SRM, represents juvenile late Mesoproterozoic (c. 1000–1200 Ma) crust associated with minor fragments of an older continental component. Evidence for an Archaean component in the basement of the SRM is lacking. As for central DML, 1100–1200 Ma extensive felsic magmatism is recognized in the SRM. Deposition of sediments during or after magmatism and possible metamorphism at 800–700 Ma is recognized from populations of detrital zircon in metasedimentary rocks. The NE Terrane of the SRM, along with the YBC, was metamorphosed under granulite-facies conditions at c. 600–650 Ma. The SW and NE Terranes of the SRM were brought together during amphibolite-facies metamorphism at c. 570 Ma, and share a common metamorphic and magmatic history from that time. High-grade metamorphism was followed by extensive A-type granitoid activity and contact metamorphism between 560 and 500 Ma. In contrast, TDM and inherited zircon core ages suggest that the LHC is a collage of protoliths with a variety of Proterozoic and Archaean sources. Later peak metamorphism of the LHC at 520–550 Ma thus represents the final stage of Gondwanan amalgamation in this section of East Antarctica.